2015
DOI: 10.3329/jom.v16i1.22399
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Antibiotic Use in Different Departments of Dhaka Medical College Hospital

Abstract: Abstract:Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Rest of the 81.82% patients was not recommended to perform any culture and sensitive test. A similar result was also observed in another study of 2015, conducted in different units of Dhaka medical college hospital, Dhaka, Bangladesh [22]. Though a number of guidelines like NHS guideline for antimicrobial protocol for the management of infection in primary care 2017-2019 and Hertfordshire partnership university NHS foundation trust guideline for antimicrobial prescribing guidelines in adults 2015 stated that clinical and diagnostic tests must be carried out before prescribing antibiotics to ensure that bacteria are responsible for the illness and prescribed antibiotics are beneficial for the illness.…”
Section: Discussionsupporting
confidence: 88%
“…Rest of the 81.82% patients was not recommended to perform any culture and sensitive test. A similar result was also observed in another study of 2015, conducted in different units of Dhaka medical college hospital, Dhaka, Bangladesh [22]. Though a number of guidelines like NHS guideline for antimicrobial protocol for the management of infection in primary care 2017-2019 and Hertfordshire partnership university NHS foundation trust guideline for antimicrobial prescribing guidelines in adults 2015 stated that clinical and diagnostic tests must be carried out before prescribing antibiotics to ensure that bacteria are responsible for the illness and prescribed antibiotics are beneficial for the illness.…”
Section: Discussionsupporting
confidence: 88%
“…Again, most of the studies done in Bangladesh, concentrate on a single disease, pathogen, or specimen. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] But, a single organism can cause different types of infection, at different sites and can cause different diseases. For example, E. coli can cause gastroenteritis, sepsis, UTI, even meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was found that 155 antibiotics were used in total of 60 patients, among which highest group of antibiotics prescribed were metronidazole (36.77%) followed by ceftriaxone (32.25) and then gentamycin (10.32%). Another study which was conducted in prescribing patterns of antibiotics in post-operative patients in teaching hospital in Hyderabad in 2014 which also had similar antibiotic prescribing pattern, among which highest group of antibiotics prescribed were third generation cephalosporin [6] comprising 44% and then 30.7% metronidazole [7].…”
Section: Discussionmentioning
confidence: 99%